Combination of Scoring Criteria and Whole Exome Sequencing Analysis of Synchronous Endometrial and Ovarian Carcinomas. Issue 4 (1st May 2018) - Yang, Lingyi; Zhang, Lin; Huang, Qiujuan; Liu, Changxu; Qi, Lisha; Li, Lingmei; Qu, Tongyuan; Wang, Yalei; Liu, Suxiang; Meng, Bin; Sun, Baocun; Cao, Wenfeng
Abstract : Objectives: The purpose of this study was to distinguish synchronous primary endometrial and ovarian carcinomas from single primary tumor with metastasis by clinical pathologic criteria and whole exome sequencing (WES). Material and Methods: Fifty-two patients with synchronous endometrial and ovarian carcinomas (SEOCs) between 2010 and 2017 were reviewed and subjected to WES. Results: On the basis of the Scully criteria, 11 cases were supposed as synchronous primary endometrial and ovarian carcinomas, 38 cases as single primary tumor with metastasis, and the remaining 3 cases (S50–S52) cannot be defined. Through a quantization scoring analysis, 9 cases that were scored 0–1 point were defined as synchronous primary endometrial and ovarian carcinomas, and 42 cases that were scored 3–8 points were defined as single primary tumor with metastasis. Two of the undefined cases were classified into metastatic disease, and another one that scored 2 points (S52) was subjected to WES. S52 was deemed synchronous primary endometrial and ovarian carcinomas, with few shared somatic mutations and overlapping copy number varieties. The finding of a serous component examined from the uterine endometrium samples further illustrated that the case was synchronous primary endometrial and ovarian carcinomas. Conclusion: By scoring criterion, SEOCs were divided into 2 groups: synchronous primary endometrial and ovarian carcinoma group and single primary tumor with metastasis group. The analysis of clonality indicated that the case that scored 2 (S52) can be considered as synchronous primary endometrial and ovarian carcinomas. Scoring criteria of clinical pathology, along with the study of the WES, may further identify the classification of SEOCs.